Depression in the patient with COPD - Wilson, Ian (Dove Medical Press, 2006)
This paper explores the recent literature surrounding comorbid depression and COPD. The literature reveals a high prevalence of depression in patients with COPD and some evidence that the depression is a result of the disease. The literature highlights the negative impact of depression on quality of life and a possible impact on mortality. Depression also negatively impacts on compliance and smoking cessation. Treatment of depression in COPD, particularly by cognitive behavioral therapy, has positive impact on quality of life. Tricyclic antidepressants have a positive impact on mood and COPD, but side effects limit their use. The advent of the new antidepressants may improve acceptability and outcomes, but the research is yet to be undertaken. Physical rehabilitation may have a positive impact on mood. This paper highlights the difficulty in screening for depression in patients with COPD due to the overlap of symptoms between the two diseases. Despite the difficulties, it is important to recognize and treat depression in patients with COPD because of the significant likelihood of improvement in quality of life.